(untitled) (Journal of Advanced Veterinary and Animal Research, 2026)
This review paper provides comprehensive insights into the current livestock production potential in the Haor regions, the impact of climate change on livestock production, development strategies for the sector, challenges associated with climate-resilient livestock farming, and potential mitigation measures. The Haors of Bangladesh, situated in the greater Sylhet and Mymensingh districts, are vital components of the ecosystem, holding significant economic, ecological, and commercial importance. The unique features of these low-lying floodplains, including their resources and seasonal variations, foster diverse biodiversity and ecosystems, covering over 1.99 million hectares and home to approximately 19.37 million people. All authors independently gathered data from peer-reviewed articles, dissertations, theses, government agencies, and media reports using PubMed, Web of Science, and Google Scholar from January 2023 to June 2025. Data were also collected through personal communication and consultation with livestock officers from the Department of Livestock Services serving in the Haor districts and relevant experts (n = 30). Climatic data were obtained from the Climate Information Management System of the Bangladesh Agricultural Research Council. Residents in Haor areas, particularly women and the elderly, are heavily engaged in livestock husbandry as a means of livelihood. The livestock sector is expected to meet nutritional requirements, generate employment, and provide national benefits through increased production of milk, meat, and eggs. This review paper is the first to synthesize, analyze, and interpret insights on the existing livestock production potential in Haor areas, along with challenges and possible mitigation strategies, culminating in some recommendations at the end of this paper. J. Adv. Vet. Anim. Res., 12(4): 1379 -1395, December 2025 http://doi.org/10.5455/javar.2025.l998